The image of man in Kazhal Ahmad’s poetry - پرۆفیسۆر دکتۆر هیمداد حوسێن بەکر; مامۆستاى یاریدەدەر سەنگەر نازم حسین (QALAAI ZANIST JOURNAL, 2021)
This Research (the image of man in Kazhal Ahmad’s poetry) is an analytical descriptive research about the view, and outlook of woman poets on man. The research consists of two chapters. In the first chapter we explained the image of man in religions, philosophers, and psychology schools. The second chapter is more practical we shed light (the image of man inKazhal Ahmad’s poetry) Finally some obtained concluding points were presented.